PSXIV-28 Performance of lambs of sheep fed diets containing narasin - de Assis, Rhaissa Garcia (J Anim Sci, 2019)
The objective of this trial was to evaluate the effects of increasing levels of narasin in the diet of lactating ewes on dry matter intake (DMI) and average daily gain (ADG) of their lambs. Forty crossbred ewes Dorper x Santa Inês with their lambs were assigned to a randomized complete block design (10 blocks and 4 treatments). The treatments were defined by the inclusion of narasin to a base diet (16.8 ± 0.66 of CP) containing 50% of concentrate and 50% of Brachiaria brizanta hay, as follow: 0N - control diet; 13N - 13 mg of narasin/kg of DM; 20N - 20 mg of narasin/kg of DM; 27N - 27 mg of narasin/kg of DM. The experiment lasted from 14 to 70 days of lactation. From the second to the tenth week of age the lambs received initial concentrate (57.0% corn; 25.0% soybean meal; 1.5% limestone; 1.5% of mineral mix; 5.0% of sugarcane molasses and 10% of milk replacer; composition: DM=89.3%; CP = 21.1%; FDN = 8.9%; FDA=2.7%) (ad libitum) in a private feeder. All data were analyzed using the MIXED procedure of SAS. The lambs were weighed weekly after 5-hours fasting. The orts were quantified weekly to determine the DMI. There was no effect of the supply of narasin to the ewes on the DMI by the lambs (0N = 0.126; 13N = 0.088; 20N = 0.153; 27N = 0.145 kg/d; P > 0.05). However, the supply of narasin decreased the ADG (0N = 269.3; 13N = 259.60; 20N = 264.02; 27 = 228.01 g; P < 0.01) of lambs. In conclusion, the use of narasin for the ewes did not benefit lamb performance.